UPAYA PENINGKATAN PENDAPATAN PEDAGANG KERUPUK DI DESA KUBU PERAHU PADA MASA COVID-19 - Yuniwati Yuniwati; Rina Milyati Yuniastuti; Riyadini Riyan Utami; Aderina Harahap (Institut Informatika dan Bisnis Darmajaya, 2022)
Community service carried out in the village of Taman Jaya Pekon Kubu Perahu, Balikpapan District, West Lampung Regency. With a population of 720 people. The service is done to cracker traders. The income of cracker traders during the Covid-19 period has decreased in their source of income, this is due to the lack of a marketing system. The results obtained in this service are that the management of natural resources has not been managed in an integrated and maximal manner, MSMEs at cracker traders have been able to manage their own business well, only for marketing it is still traditional in the sense that they have not used social media. The community has implemented health protocols for a long time. pandemic and MSME workers have started to use masks and wash their hands and keep their distance in carrying out their activities. For the people of the Taman Jaya Apekon Kubu Perahu village, in order to increase the sense of concern between the community to make the village more developed, improve facilities and infrastructure for learning in the field of science and technology and be able to manage natural and human resources, it must be managed with integrity so that it can run optimally. and for better village development. Keywords— Income. Technology, Social Media